Solvent Extraction and Characterization of Neutral Lipids in Oocystis sp. - Anthony, Renil; Stuart, Ben (Frontiers in Energy Research, 2015)
Microalgae are a favorable feedstock for bioproducts and biofuels due to their high oil content, fast growth rates, and low resource demands. Solvent lipid extraction efficiency from microalgae is dependent on algal strain and the extraction solvent. Four non-polar extraction solvents were evaluated for the recovery of neutral cellular lipids from microalgae Oocystis sp. (University of Texas at Austin LB2396). Methylene chloride, hexane, diethyl ether, and cyclohexane were selected as the extraction solvents. The lipid extracts were derivatized and analyzed using gas chromatography–mass spectroscopy. All solvent extracts contained hexadecanoic acid, linoleic acid, and linolenic acid; accounting for 70% of total lipid content with a proportional wt% composition of the three fatty acids, except for the hexane extracts that showed only hexadecanoic acid and linoleic acid. While not statistically differentiated, methylene chloride proved to be the most effective solvent for Oocystis sp. among the four solvents tested with a total average neutral lipid recovery of 0.25% of dry weight followed by diethyl ether (0.18%), cyclohexane (0.14%), and hexane (0.11%). This research presents a simple methodology to optimize the selection of lipid specific extraction solvents for the microalgal strain selected.